2012
DOI: 10.1186/1471-2156-13-15
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic rainbow trout linkage map provides new insights into the salmonid whole genome duplication and the conservation of synteny among teleosts

Abstract: BackgroundRainbow trout is an economically important fish and a suitable experimental organism in many fields of biology including genome evolution, owing to the occurrence of a salmonid specific whole-genome duplication (4th WGD). Rainbow trout is among some of the most studied teleosts and has benefited from substantial efforts to develop genomic resources (e.g., linkage maps. Here, we first generated a synthetic map by merging segregation data files derived from three independent linkage maps. Then, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
74
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 37 publications
5
74
1
1
Order By: Relevance
“…Studies on comparative mapping have revealed that the rates of nucleotide sequence similarity were positively correlated with phylogenetic relationships among fish species (Xia et al 2010;Zheng et al 2011;Guyomard et al 2012). In this study, we found that bighead carp (Hypophthalmichthyinae) genome has a higher similarity with common carp (Cyprininae) (95.3 %) than that with zebrafish (Danioninae) (70.9 %).…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…Studies on comparative mapping have revealed that the rates of nucleotide sequence similarity were positively correlated with phylogenetic relationships among fish species (Xia et al 2010;Zheng et al 2011;Guyomard et al 2012). In this study, we found that bighead carp (Hypophthalmichthyinae) genome has a higher similarity with common carp (Cyprininae) (95.3 %) than that with zebrafish (Danioninae) (70.9 %).…”
Section: Discussionsupporting
confidence: 46%
“…With the assistance of comparative mapping, these chromosomal rearrangements could be easily observed. Inversion and translocation are quite common among different species, and they have been observed in all previously investigated fishes, including zebrafish , medaka (Kasahara et al 2007), rainbow trout (Guyomard et al 2012) and common carp (Zhang et al 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, although fishes were reported as having high rates of chromosomal rearrangements and low rates of synteny within vertebrates (Robinson-Rechavi et al, 2001a, 2001bVenkatesh, 2003;Ravi & Venkatesh, 2008), more recent investigation indicated both the presence of large syntenic blocks within Teleosts and between Teleosts and other vertebrates (Mazzuchelli et al, 2012). This indicates the stability of the genome of these fishes over long evolutionary time scales (Guyomard et al, 2012;Schartl et al, 2013). In addition a higher conserved gene order was observed in fishes than in mammals by genome comparison of three teleost species (fugu, Tetraodon, and medaka) with those of three mammalian lineages (human, mouse, and opossum), and authors reported these results as "largely due to a lower rate of interchromosomal rearrangements in the teleosts" (Kai et al, 2011).…”
Section: Discussionmentioning
confidence: 99%